Adapting and Enduring: Lessons Learned from International School Educators During COVID-19. (August 2021) - Doll, Kathleen; Ragan, Moira; Calnin, Gerard; Mason, Sarah; House, Kevin
With the outbreak of COVID-19 in early 2020, school buildings across the globe closed, leading educators, students and families to transition rapidly to online education. It is clear that schools will in the future continue to employ online learning, even as students and educators return to school buildings. While the education community has over a number of years generated a range of practical tips and guidance about online education—especially since the onset of COVID-19—many are not supported by research (DiPietro et al., 2010) and neglect international school settings (Barbour, 2014). This study investigates the experiences of sixty-one K-12 international educators via nineteen focus groups, contributing to the literature base on pedagogical, leadership and practical strategies needed to support effective online learning. Four lessons learned emerged from the data: technological challenges are exacerbated during a crisis; educators adapted to revise pedagogical strategies when under pressure; student and parent experiences were inconsistent and complex; and school leaders play an important role during a transition to online education. Although COVID-19 posed challenges, educators are resilient, adaptable, and deeply committed to student learning. School leaders now have an opportunity to reconstruct a model of education which offers students the best of face-to-face learning augmented by the most effective use of virtual technologies. This is more than planning for potential crises; this is reimagining the future of education.